Optimization of the functional-spatial structure of the nature reserve fund for ecological network planning in Vinnitsa region - Elisavenko, Yu., Khmelnytskyi National University, Khmelnytskyi (Ukraine) (Stiinta Agricola, 2013)
The article is devoted to the problem regarding the formation of the transboundary ecological network of Vinnitsa region and the Republic of Moldova. The subject of the research was the transboundary nature reserve fund of Vinnitsa region and the Republic of Moldova, which represents the basis for the ecological network formation. We used analytical and cartographical methods in order to estimate the optimum structural parameters of the nature reserve fund. It was found out that the nature reserve fund that is situated in the transboundary region "Dniester" is not optimal for the ecological network formation. The article also provides some recommendations on the optimal structure formation of the nature reserve fund according to the principles of sustainable development.